Porphyrin-bile acid conjugates: from saccharide recognition in the solution to the selective cancer cell fluorescence detection - Králová, Jarmila; Koivukorpi, Juha; Kejík, Zdenek; Poucková, Pavla; Sievänen, Elina; Kolehmainen, Erkki; Král, Vladimír (Organic & biomolecular chemistry, 2008)
This paper describes the preparation and use of conjugates of porphyrins and bile acids as ligands to bind to tumor expressed saccharides. Bile acid-porphyrin conjugates were tested for recognition of saccharides that are typically present on malignant tumor cells. Fluorescence microscopy, in vitro PDT cell killing, and PDT of subcutaneous 4T1 mouse tumors is reported. High selectivity for saccharide cancer markers and cancer cells was observed. This in vivo and in vitro study demonstrated high potential use for these compounds in targeted photodynamic therapy.
Keywords: Apoptosis; transformované buněčné linie; Ligands; sacharidy; fotochemoterapie; Bile Acids and Salts; Microscopy, Fluorescence; senzitivita a specificita; 3T3 Cells; zvířata; ligandy; Molecular Structure; vazebná místa; fluorescenční mikroskopie; Biomarkers, Tumor; Animals; lidé; Drug Screening Assays, Antitumor; HeLa Cells; myši inbrední BALB C; screeningové testy protinádorových léčiv; Glycosylation; nádorové biomarkery; buňky 3T3; Mice; apoptóza; žlučové kyseliny a soli; Carbohydrates; Neoplasms; Cell Line; glykosylace; Cell Proliferation; Cell Line, Transformed; Mice, Inbred BALB C; Dose-Response Relationship, Drug; Porphyrins; proliferace buněk; Humans; HeLa buňky; Sensitivity and Specificity; buněčné linie; myši; nádory; molekulární struktura; DNA Fragmentation; Photochemotherapy; Structure-Activity Relationship; Binding Sites; roztoky; vztah mezi dávkou a účinkem léčiva; Solutions; fragmentace DNA; porfyriny; vztahy mezi strukturou a aktivitou